Greenhouse gas emissions during timber and concrete building construction —A scenario based comparative case study. (April 2018) - Sandanayake, Malindu; Lokuge, Weena; Zhang, Guomin; Setunge, Sujeeva; Thushar, Quddus
Highlights: Timber reduce GHG emissions from materials and transportation during construction. Equipment GHG emissions are not affected with the change of materials. Use of regional materials has major influence on GHG emissions. Material recycling reduce GHG emissions during timber and concrete construction. Abstract: Greenhouse gas (GHG) is a major air emission pollutant that creates environmental burden in buildings. Timber buildings are gaining notable popularity in the building industry due to life cycle environmental and economic benefits over conventional buildings. However, little or no studies have made attempts to compare greenhouse gas emission variations in timber and concrete buildings during the construction stage. Knowledge of emission at the construction stage is critical for passionate contractors who wants to maintain an environmental friendly built environment. The study presented in this paper aims to compare GHG emissions and energy consumptions during timber and concrete building construction. A process based quantitative assessment is conducted for evaluating emissions from materials, equipment and transportation stages. The comparative results of the study indicated that use of timber can reduce embodied emissions as well as transportation emissions during the construction stage. Scenario analyses results comprehends that recycling of materials and use of regional materials influence GHG emissions the most while transportation distance has medium effect on total GHG emissions at the construction stage of timber building. The results of the study are important in aggregate level decision making of timber and concrete buildings. Further studies are encouraged on conducting comprehensive assessment of different timber usages in a building to investigate the GHG emission variation.